Biochemical and Electron Microscopic Changes Induced by Giardia in Experimentally Infected Lambs - Elmadawy, Reham Samir; Radwan, Mervat E.I; Mahmoud, Mohamed Abd El-Aziz (International Journal of Veterinary Sciences Research, 2016)
The present study was conducted to evaluate the effect of Giardia on the biochemical serum constituents of experimentally infected lambs, in addition to studying the observed alterations accompanying Giardia infection in the intestinal mucosa using scanning electron microscopy. Twenty lambs were allotted into two equal groups, Group A ( non infected) was kept as control negative and Group B (infected) was orally inoculated by 104 Giardia cysts. The biochemical changes were assessed in both groups on 7th. 14th, 21th and 30th days post inoculation (dpi). The study disclosed that Giardia induced a significant drop in the levels of serum electrolytes (chloride,sodium, potassium and calcium), blood glucose, different enzymes (lipase, amylase and alkaline phosphatase). Furthermore, the levels of urea, liver enzymes (alanine aminotransferase and aspartate aminotransferase), inflammatory marker (C-reactive protein) and oxidative stress marker (malondialdehyde) were elevated, but nitric oxide was declined by 30th dpi. The scanning electron microscopy of the intestinal mucosa of the infected lambs revealed a notable alteration which was fully explained. All the presented results interpret the pathophysiological effect of Giardia which adversely affects the health status of lambs.